Conventional to organic transition of Citrus x sinensis (L.) Osbeck (pro. sp.) orchards in municipalities of northern Veracruz state - Zamora Juárez, Sherell; Rodríguez-Lagunes, Daniel Arturo; Bustillo-García, Lissette Cristina; Castañeda-Castro, Odón; Núñez-Pastrana, Rosalía; Noa-Carrazana, Juan Carlos; Osorio-Acosta, Francisco (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
This research determined the degree of transition towards organic production and management of Valencia orange in the municipalities of northern Veracruz State. One hundred and six surveys were administered to producers grouped into four consolidated civil associations. A constructed transition index considering six variables revealed an average of 0.768. Citrus grower/institution positively correlated with intercropping (p = 0.0281) and with internal factors (p = 0.0257). Determinant factors for transition index were intercropping (p = 0.00009), and citrus grower/institution interaction (p = 0.0000). These internal and external factors together with years of conversion, averaging six years, resulted in an intermediate transition degree towards organic Valencia orange production. Municipalities of northern Veracruz State stand on varying degrees of transition towards organic agriculture. Yet, many growers still conserve some management practices not consistent with organic production. Highlights: Transition index to organic agriculture of citrus growers was 0.768. Some citrus growers with few years of organic production apply all practices as advanced or organic. Growers of northern Veracruz, Mexico are in intermediate transition degree towards organic Valencia orange production.